Epidemiological factors impacting the development of Wheat streak mosaic virus outbreaks - Webb, Christian A. (Kansas State University, 2018)
Wheat streak mosaic (WSM) is a devastating disease of winter wheat (Triticum aestivum L.) in Kansas. Although WSM can cause heavy crop losses, the severity of regional and statewide losses varies by year and location. Wheat streak mosaic is caused primarily by the Wheat streak mosaic virus (WSMV) and is spread by the wheat curl mite, Aceria tosichella Keifer. To infect fall planted wheat, both the virus and mite require a living, grass host to survive the summer months. The first research objective was to determine the risk of different grass species to serve as a source of WSM. Published experiments and surveys were reviewed to determine the suitability of each host based on a set of criteria. An analysis of the reports from the reviewed literature found 39 species to host both pests. Categorical analysis of these observations suggested that well-studied grass species could be placed in four risk groupings with ten species at high risk of carrying both pests. Furthermore, results from controlled experimentation generally agrees with results from field survey results for both pests. The second objective was to determine the weather and cropping factors that are associated with regional epidemics of WSM in Kansas. Historic disease observations, weather summaries, soil moisture indices, and cropping statistics were collected from Kansas crop reporting districts from 1995-2013. Binary response variables (non-epidemic case vs epidemic cases) were developed from different thresholds of district losses attributed to WSM. Variables associated with WSM epidemics were identified by a combination of non-parametric correlation, classification trees, and logistic regression. This analysis indicates that the total acres of wheat planted per season was associated with the low frequency of epidemics in Eastern Kansas. Temperature during September appears to influence the yield losses caused by WSM. Wheat planting generally begins during September and continues through October in the state. Temperature during the winter months (December-February) was also identified as important with warm conditions favoring outbreaks of disease. Dry soil conditions in February was also associated with epidemics of WSM. Models combining these variables correctly classified 60 to 74% of the cases considered in this analysis.
Keywords: Wheat streak mosaic virus; Wheat curl mite; Aceria tosichella; Epidemiology; Alternate Hosts; Triticum aestivum